ANALISIS DAMPAK PEMBAYARAN NON TUNAI TERHADAP JUMLAH UANG BEREDAR DI INDONESIA - Lasondy Istanto S Istanto S; Syarief Fauzie (Ekonomi dan Keuangan, 2014)
This research has a purpose to analyze impact of non-cash payment to money supply in Indonesia. Money supplies used in this research are narrow money (M1) and broad money (M2). Non-cash payment in this research represented by four transaction scheme, card-based payment system (APMK), e-money, Bank Indonesia’s national clearing system (SKNBI), and BI-RTGS system.Error correction model is applied in order to study the relationship between money supply and non-cash payment system. The result shows thatthe volume of credit card transactions, the value of ATM/Debit transaction, the value of e-money transaction, the volume of SKNBI transaction, and the value of BI-RTGS transaction has positive effect on M1, while the value of SKNBI transactions has negative effect on M1. Meanwhile by substituting M1 to M2 the results shows that, the volume and value of ATM/Debit transaction, the volume of SKNBI transaction, the volume and value of BI-RTGS transactions has positive effect on M2 while the value of e-money transactions and value of SKNBI transaction has negative effect on M2.Key Word: Money Supply, M1, M2, Non-Cash Payment, ECM.